Transgenic short-QT syndrome 1 rabbits mimic the human disease phenotype with QT/action potential duration shortening in the atria and ventricles and increased ventricular tachycardia/ventricular fibrillation inducibility. (28th November 2018) - Odening, Katja E; Bodi, Ilona; Franke, Gerlind; Rieke, Raphaela; Ryan de Medeiros, Anna; Perez-Feliz, Stefanie; Fürniss, Hannah; Mettke, Lea; Michaelides, Konstantin; Lang, Corinna N; Steinfurt, Johannes; Pantulu, Naga Deepa; et al.
Abstract: Aims: Short-QT syndrome 1 (SQT1) is an inherited channelopathy with accelerated repolarization due to gain-of-function in HERG/ I Kr . Patients develop atrial fibrillation, ventricular tachycardia (VT), and sudden cardiac death with pronounced inter-individual variability in phenotype. We generated and characterized transgenic SQT1 rabbits and investigated electrical remodelling. Methods and results: Transgenic rabbits were generated by oocyte-microinjection of β-myosin-heavy-chain-promoter-KCNH2/HERG-N588K constructs. Short-QT syndrome 1 and wild type (WT) littermates were subjected to in vivo ECG, electrophysiological studies, magnetic resonance imaging, and ex vivo action potential (AP) measurements. Electrical remodelling was assessed using patch clamp, real-time PCR, and western blot. We generated three SQT1 founders. QT interval was shorter and QT/RR slope was shallower in SQT1 than in WT (QT, 147.8 ± 2 ms vs. 166.4 ± 3, P < 0.0001 ). Atrial and ventricular refractoriness and AP duration were shortened in SQT1 (vAPD90, 118.6 ± 5 ms vs. 154.4 ± 2, P < 0.0001 ). Ventricular tachycardia/fibrillation (VT/VF) inducibility was increased in SQT1. Systolic function was unaltered but diastolic relaxation was enhanced in SQT1. I Kr -steady was increased with impaired inactivation in SQT1, while I Kr -tail was reduced. Quinidine prolonged/normalized QT and action potential duration (APD) in SQT1 rabbits by reducing I Kr . Diverse electrical remodelling was observed: in SQT1, I K1 was decreased—partially reversing the phenotype—while a small increase in I Ks may partly contribute to an accentuation of the phenotype. Conclusion: Short-QT syndrome 1 rabbits mimic the human disease phenotype on all levels with shortened QT/APD and increased VT/VF-inducibility and show similar beneficial responses to quinidine, indicating their value for elucidation of arrhythmogenic mechanisms and identification of novel anti-arrhythmic strategies.